2016
DOI: 10.3140/bull.geosci.1509
|View full text |Cite
|
Sign up to set email alerts
|

Architecture, paleosols and cyclicity of the Middle- Late Pennsylvanian proximal fluvial system (Nyřany Member, Pilsen Basin, Czech Republic)

Abstract: The Nýřany Member in the Pilsen Basin records the evolution of a broad paleotropical alluvial plain that preserves amalgamated lenticular to sheet sandstone bodies separated by basin-wide floodplains. Facies and architectural element analysis in conjunction with well-log correlation was employed in order to reconstruct fluvial system stacking patterns and decipher the controls responsible for the preserved fluvial architectures and identify the possible influence of allogenic processes on basin fill architectu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…et al 2018), or N (Martínek et al 2017), the results of our study of K-feldspars give evidence at least for the source of big arkoses feldspars to be NW in the area of today's Karlovy Vary Massif both for the whole time of sedimentation (314.2-297.1 Ma; Moscovian-Asselian) and in the whole basin range up to a minimal distance of 90 km from the source (along the line Budyně nad Ohří -Velvary -Kladno). The same direction of input (NW) was unambiguously confirmed by sedimentological study of the Nýřany Member sediments in the Kaznějov quarry with application of paleofluvial analyses (Lojka et al 2016).…”
Section: Figure 5b Graphs Of Ba/rb (Ppm) Contents Of K-feldspars In P...mentioning
confidence: 54%
See 1 more Smart Citation
“…et al 2018), or N (Martínek et al 2017), the results of our study of K-feldspars give evidence at least for the source of big arkoses feldspars to be NW in the area of today's Karlovy Vary Massif both for the whole time of sedimentation (314.2-297.1 Ma; Moscovian-Asselian) and in the whole basin range up to a minimal distance of 90 km from the source (along the line Budyně nad Ohří -Velvary -Kladno). The same direction of input (NW) was unambiguously confirmed by sedimentological study of the Nýřany Member sediments in the Kaznějov quarry with application of paleofluvial analyses (Lojka et al 2016).…”
Section: Figure 5b Graphs Of Ba/rb (Ppm) Contents Of K-feldspars In P...mentioning
confidence: 54%
“…These conclusions were first evidenced by field observation (Jiránek 1976): (1) alternation of kaolin beds and non-kaolinized arkoses (0.X-X m) in the lower parts of the deposits of Horní Bříza and Kaznějov; (2) abundant intercalations of kaolinitic clays and siltstones (often of dark red colour), representing redeposited earlier kaolinized material, which would moreover have been a barrier to penetrating kaolinization solutions in the case of postsedimentary kaolinization (Lojka et al 2016 found also interlayers of paleosoils); (3) findings of fresh feldspar clasts inside intensively kaolinized rocks, which Kužvart (1969) incorrectly considered as a proof of post-sedimentary kaolinization; and (4) geochemical characteristics, non-corresponding to the primary kaolinic profiles (irregular distribution of the major and trace elements in the vertical profile, common growth of trace elements, alkalis, and REE with the declining content of kaolinite; Jiránek 1982b). While the content of kaolinite in this type of sediments (i. e. in differently granular sandstones and conglomerates) does not change with the depth due to the fluent contribution of already kaolinized material, in the case of post-sedimentary kaolinization of arkoses the kaolinite content should distinctly decline with the depth.…”
Section: Notes On the Genesis Of Kaolin Deposits In Arkoses Of Permo-...mentioning
confidence: 94%
“…This climatic complexity is evident not only from the sedimentary record and paleosols (Driese & Ober 2005;Rosenau et al 2013a, b;Allen et al 2014;Opluštil et al 2015;Lojka et al 2009Lojka et al , 2016, but also from time-coinciding changes of terrestrial biota (e.g. Falcon-Lang et al 2009, 2011DiMichele et al 2006DiMichele et al , 2008DiMichele 2014).…”
Section: Discussionmentioning
confidence: 99%
“…But, as emphasised by Miall (1996), in for ma tion about the floodplain of this river sys tem is lim ited, with no de tailed data whether or not crevassing and cre vasse splays are com mon. Braided flu vial sys tems may have well-de vel oped overbank ar eas, where thick pack ages of overbank fines ac cu mu late (Ielpi et al, 2014;Lojka et al, 2016) in places con tain ing thick coal seams (Doktor, 2007;Kêdzior, 2016). The area stud ied dur ing Early Ju ras sic time was prob a bly lo cated near the trop ics and a hot and wet cli mate was con trolled by sea sonal, mon soonal type heavy rain fall (Popa and Van Konijnenbrug-Van Cittert, 2006;Kêdzior and Popa, 2013), thus rapid ero sion and ef fi cient run off occurred only pe ri od i cally.…”
Section: Depositional Environment Of the Mehadia Section Depositsmentioning
confidence: 99%